Lack of desensitization of the cough reflex in ovalbumin-sensitized rabbits during exercise. - Angelica Tiotiu; Bruno Chenuel; Laurent Foucaud; Bruno Demoulin; Silvia Demoulin-Alexikova; Christo Christov; Mathias Poussel (PLoS ONE)
Introduction Cough is a major symptom of asthma frequently experienced during exercise but little is known about interactions between cough and exercise. The goal of our study was to clarify the potential modulation of the cough reflex (CR) by exercise in a spontaneously breathing anaesthetized animal model of airway eosinophilic inflammation. Materials & methods Ten ovalbumin (OVA) sensitized adult rabbits and 8 controls were studied. The ventilatory response to direct tracheal stimulation, performed both at rest and during exercise was determined to quantify the incidence and the sensitivity of the CR. Broncho-alveolar lavages (BAL) and cell counts were performed to assess the level of the airway inflammation following OVA-induced sensitization. Exercise was mimicked by Electrically induced hindlimb Muscular Contractions (EMC). Results Among 494 tracheal stimulations, 261 were performed at rest and 233 at exercise. OVA challenges in sensitized rabbits caused a significant increase in the percentage of eosinophils (p = 0.008) in BAL. EMC increased minute ventilation by 36% and 35% in OVA and control rabbits respectively, compared to rest values. The sensitivity of the CR decreased during exercise compared to baseline in control rabbits (p = 0.0313) while it remained unchanged in OVA rabbits. Conclusion The desensitization of the CR during exercise in control rabbits was abolished in OVA rabbits. The precise role of airway inflammation in this lack of CR desensitization needs to be further investigated but it might contribute to the exercise-induced cough in asthmatics.